Exome Sequencing of Paired Colorectal Carcinomas and Synchronous Liver Metastases for Prognosis and Therapy Prediction - Hlaváč, Viktor; Červenková, Lenka; Šůsová, Simona; Holý, Petr; Liška, Václav; Vyčítal, Ondřej; Šorejs, Ondřej; Fiala, Ondřej; Daum, Ondřej; Souček, Pavel (JCO precision oncology, 2023)
PURPOSE: Analysis of somatic variant profiles in retrospectively collected pairs of primary tumors and synchronous liver metastases from surgically treated patients with colorectal carcinomas. Mutational profiles were compared between groups of patients stratified by response to chemotherapy and survival. PATIENTS AND METHODS: The study used whole-exome sequencing of tumor sample pairs from 20 patients diagnosed and treated at a single center. The Cancer Genome Atlas COAD-READ data set (n = 380) was used for validation in silico, where possible. RESULTS: The most frequently altered oncodrivers were APC (55% in primaries and 60% in metastases), TP53 (50/45), TRIP11 (30/5), FAT4 (20/25), and KRAS (15/25). Harboring variants with a high or moderate predicted functional effect in KRAS in primary tumors was significantly associated with poor relapse-free survival in both our sample set and the validation data set. We found a number of additional prognostic associations, including mutational load, alterations in individual genes, oncodriver pathways, and single base substitution (SBS) signatures in primary tissues, which were not confirmed by validation. Altered ATM, DNAH11, and MUC5AC, or a higher share of SBS24 signature in metastases seemed to represent poor prognostic factors, but because of a lack of suitable validation data sets, these results must be treated with extreme caution. No gene or profile was significantly associated with response to chemotherapy. CONCLUSION: Taken together, we report subtle differences in exome mutational profiles between paired primary tumors and synchronous liver metastases and a distinct prognostic relevance of KRAS in primary tumors. Although the general scarcity of primary tumor-synchronous metastasis sample pairs with high-quality clinical data makes robust validation difficult, this study provides potentially valuable data for utilization in precision oncology and could serve as a springboard for larger studies.
Keywords: prognóza; sekvenování exomu; protoonkogenní proteiny p21(ras); individualizovaná medicína; Proto-Oncogene Proteins p21(ras); Colorectal Neoplasms; Neoplasm Recurrence, Local; Prognosis; Retrospective Studies; kolorektální nádory; retrospektivní studie; lidé; Exome Sequencing; Precision Medicine; Liver Neoplasms; lokální recidiva nádoru; nádory jater; Humans